IMPROVING STUDENT LEARNING OUTCOMES THROUGH TEAM QUIZ MODEL ON HUMAN EXCRETION SYSTEM MATERIAL FOR CLASS VIII.3 MTSN KOTA SOLOK - Yetti Laswita Putri (Department of Science Education, 2022)
Fun learning can create new colors in the learning process. So that the learning objectives will be achieved. Especially in the subjects of Natural Sciences (IPA), the concept of learning in principle is close to real life. However, students still have difficulty understanding the concepts. Because they think that learning science is identical to mathematics because there are formulas that use numbers. The team quiz learning model can have an impact on the science learning process, this can be seen from student learning outcomes which have increased by about 10% from cycle one to cycle two, and students' ability to build communication can be seen from the teamwork formed in compiling quiz questions. will be submitted to another pair.